Can PDIA become a regular part of how a government works? - Building S tate Capability - Harrington, Peter (2022)
Institutional change is part of the theory of change of PDIA – scaling through the diffusion of new ways of thinking and greater problem-sol ving know-how. And once a community of practice reaches critical mass across an eco-system, a tipping point can happen where the eco-system becomes generally more open to novelty, where success is a more effect ive route to legitimacy, and where leadership is oriented towards valu e creation.